2022
DOI: 10.7759/cureus.28285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Value of Hematologic Parameters and Ratios in SARS-CoV-2 VOC-202012/01 Mutant Population

Abstract: In this study, we set out to study possible differences between individuals with and without VOC 202012/01 variant by using less costly complete blood count analytes and quickly analyzing the samples and ratios derived from these analytes. For this purpose, we assessed neutrophil, lymphocyte, platelet, and Red Blood Cell Distribution Width-Standard Deviation (RDW-SD) levels among complete blood count parameters (CBC) (identification and count of red blood cell, neutrophil, eosinophil, basophil, lymphocyte, mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although some studies have confirmed that the Omicron variant has a lower prevalence of pneumonia than other strains and primarily targets the upper respiratory tract, this does not imply that the Omicron variant lacks clinical pathogenicity [ 27 , 28 ]. A previous study found that using cost-effective complete blood parameters and their derived hematological profiles can predict the clinical conditions of patients with COVID-19 variants, as well as their need for hospitalization or ICU admission [ 29 ]. During the early stages of the COVID-19 pandemic with the wild-type variant, our research team focused on less costly complete blood parameters to assess the clinical value of these indicators in patients at high risk of severe cases [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have confirmed that the Omicron variant has a lower prevalence of pneumonia than other strains and primarily targets the upper respiratory tract, this does not imply that the Omicron variant lacks clinical pathogenicity [ 27 , 28 ]. A previous study found that using cost-effective complete blood parameters and their derived hematological profiles can predict the clinical conditions of patients with COVID-19 variants, as well as their need for hospitalization or ICU admission [ 29 ]. During the early stages of the COVID-19 pandemic with the wild-type variant, our research team focused on less costly complete blood parameters to assess the clinical value of these indicators in patients at high risk of severe cases [ 41 ].…”
Section: Introductionmentioning
confidence: 99%